Three-dimensional structural and metric characterisation of cardioids - Geyer, Stefan H.; Ceci Ginistrelli, Lavinia; Ilmer, Tobias; Schwendt, Karoline M.; Mendjan, Sasha; Weninger, Wolfgang J. (Frontiers in Cell and Developmental Biology, 2024)
Exact three-dimensional (3D) structural information of developing organoids is key for optimising organoid generation and for studying experimental outcomes in organoid models. We set up a 3D imaging technique and studied complexly arranged native and experimentally challenged cardioids of two stages of remodelling. The imaging technique we employed is S-HREM (Scanning High Resolution Episcopic Microscopy), a variant of HREM, which captures multiple images of subsequently exposed surfaces of resin blocks and automatically combines them to large sized digital volume data of voxels sizes below 1 µm 3 . We provide precise volumetric information of the examined specimens and their single components and comparisons between stages in terms of volume and micro-and macroanatomic structure. We describe the 3D arrangement and lining of different types of cavities and their changes between day 10 and day 14 and map the various cell types to their precise spatial and structural environment. Exemplarily, we conducted semiautomatic counts of nuclei. In cryo-injured cardioids, we examined the extension and composition of the injured areas. Our results demonstrate the high quality and the great potential of digital volume data produced with S-HREM. It also provides sound metric and structural information, which assists production of native and experimentally challenged left ventricle cardioids and interpretation of their structural remodelling.